2012
DOI: 10.1002/pen.23100
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time crystalline orientation measurements during low‐density polyethylene blown film extrusion using wide‐angle X‐ray diffraction

Abstract: Real‐time wide‐angle X‐ray diffraction studies were successfully used to investigate the effect of film blowing process parameter on the crystalline orientation development during the blown film extrusion of low‐density polyethylene. Azimuthal distribution scans showed the evolution of crystalline orientation in the bubble from an isotropic state to an oriented state as inferred from (110) and (200) planes. These real‐time X‐ray diffraction measurements in a blown film line are consistent with prior observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Film blowing is one of the most important polymer processing technologies and is extensively used to produce packaging films, protective films, and agriculture films. The world production of agriculture films was nearly 3.82 million tons in the year of 2016. During film blowing, the polymer melt is extruded from an annular die and then blown up to form a tubular film or bubble, during which the film is biaxially stretched with large deformation and cooled by an air ring. For semicrystalline polymers like polyethylene (PE), both cooling and stretching promote crystallization, which eventually results in a stable tubular bubble without further plastic deformation. The position where no further deformation occurs to the bubble is defined as the frost line position. , Below the frost line position, complex flow and temperature field are imposed on the melt or semisolid polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Film blowing is one of the most important polymer processing technologies and is extensively used to produce packaging films, protective films, and agriculture films. The world production of agriculture films was nearly 3.82 million tons in the year of 2016. During film blowing, the polymer melt is extruded from an annular die and then blown up to form a tubular film or bubble, during which the film is biaxially stretched with large deformation and cooled by an air ring. For semicrystalline polymers like polyethylene (PE), both cooling and stretching promote crystallization, which eventually results in a stable tubular bubble without further plastic deformation. The position where no further deformation occurs to the bubble is defined as the frost line position. , Below the frost line position, complex flow and temperature field are imposed on the melt or semisolid polymer.…”
Section: Introductionmentioning
confidence: 99%
“…As the draw ratio increases, a severe increment of the fiber stiffness can be observed; furthermore, as documented by the results depicted in Figure 9B, a concurrent increment of the tensile stress and a drastic decrease of the fiber ductility verify as a consequence of drawing. Several studies have shown that the macromolecular orientation induces, in turn, an increase of the polymer crystallization rate and modification of the crystal structures, as well [110][111][112]. For instance, in the case of polypropylene-based materials, an elongationinduced evolution of the crystalline structure from a spherulitic to a cylindritic morphology was documented [113].…”
Section: Effect Of Elongational Flow In Modifying Morphology and Mechanical Properties Of Homogeneous Polymersmentioning
confidence: 99%
“…Therefore, with the continuous development of detection methods, some researchers have tried to in situ study the film blowing process by using synchrotron radiation technology in recent years . Giri Gururajan and coworkers used WAXD technology to establish a real‐time detection measurement, which is possible to detect the structure of bubble during blown film process, and roughly plot the LDPE bubble crystallization and orientation curve. Van Drongelen and Troisi used WAXD measurement and the first time used SAXS technology in situ to detect the structural evolution of several different molecular structure of PE at different processing conditions.…”
Section: Introductionmentioning
confidence: 99%